(untitled) (Bangladesh Journal of Botany, 2018)
The effects of various carbon and nitrogen sources were evaluated on production of proteases by Bacillus subtilis IC-5. Both type and concentration of carbon and nitrogen sources influenced the production of proteases. Among the carbon sources glucose was found to be the most effective. It gave maximum production at 2% w/v concentration i.e., 1875 and 950 U/ml, alkaline and neutral protease, respectively. The response of Bacillus subtilis IC-5 towards synthesis and excretion of enzymes varied with the type of nitrogen sources. The addition of organic nitrogen sources to basal medium repressed the synthesis of proteases while the addition of inorganic nitrogen source such as sodium nitrate was found to be the best stimulating for alkaline and neutral protease synthesis. Sodium nitrate enhanced the production up to 62.40 and 10.52% of alkaline and neutral protease, respectively against w.r.t. control.